Analisis Kemampuan Peserta Didik Dalam Memecahkan Masalah Konsep Gerak Berbentuk Grafik Dengan Tes Diagnostik pada Siswa SMP - Murtayasa, Wayan; Sahara, La; Eso, Rosliana (Jurusan Pendidikan Fisika, 2019)
In this study aims to describe the ability and difficulty profile of students in solving graphic motion concept problems using diagnostic tests on grade VIII students of SMP Negeri 10 Kendari. The method used in this research is descriptive method. The subjects in this study were 30 students of class VIII3 of Junior High School 10 Kendari in the 2018/2019 school year and conducted in May 2019. Data collection techniques in this study were carried out by providing research instruments in the form of description tests. Data analysis techniques in the form of analysis of the results of tests of ability and difficulty associated with solving graphical problems. The results of this study indicate that the average ability of students in solving graphic motion concepts is less category with each interpretation ability of 10.14%, interpolation of 30%, extractpolation of 16.66% and transformation ability of 19, 11%. To profile the difficulties of students based on the KKM achievement, students still experience difficulties for all indicators with the average category being the weak category. While the difficulty profile is based on the material profile, students still experience difficulties for all sub materials with an average weak category.